Translation Quality Of English-Indonesian By Using Google Translate - Cromico, Jimmy; , Dr. Anam Sutopo, M.Hum; , Dr. Dwi Haryanti, M.Hum (2015)
The purposes of this research are to identify the technique of translating used in Google Translate, to describe the accuracy of translation result by using Google Translate. to clarify the acceptabilty of translation result by using Google Translate. The last to describe the readability of translation result by using "Google Translate".This research belongs to a qualitativeresearchemployingdescriptive method. It aims to describe the translation techniques occursinthe translation andthe quality assessmentthat covers accuracy, acceptability and readability of the sentences of the scientific articles by Google Translate.The data in this research are all sentences from those articles taken as data. This research was conducted based on first and second data. The first data consists of 106 sentences taken from three articles.The second data were taken by distributing questionnaire to some raters.The analysis shows that Google Translate applied 10 kinds of translation techniques in translating the scientific articles. The techniques are calque there are 2 data or (1,41%), borrowing there are 24 data or (16,90%), word for word there are 55 data or (38,73%)., literal translation there are 35 data or (24,65%), transposition there is 1 data or ( 0,70%)., amplification there are 2 data or (1,41%), reduction there are 2 data or (1,41%), generalization there are 5 data or (3,52%), particularization there are 2 data or (1, 41%) and naturalization there are 9 data or (6, 34%).The analysis on accuracy shows that there are 16 data or (15, 10%) considered to be accurate, 61 data or (57, 54%) considered to be less accurate, and 29 data considered in accurate.It means that in general the translation is less accurate.The analysis on acceptability shows that there are 28 data or (26, 41%) considered to be acceptable, 67 data or (63, 21%) considered to be less acceptable, and 11 data or (10,38%) considered to be unacceptable.The analysis on readability shows that there are 13 data or (12, 27%) considered to be readable, 47 data or (44, 33%) considered to be less readable, and 46 data or (43, 30%) considered to be unreadable.The analysisshows that implementation of techniques makes the translation less accurate, less acceptable and less readable. It means that Google Translate can not determine a suitable techniques to produce a quality translation in translating sentences found on scientific articles.